Elucidation and Evaluation of Substituted Pyrimidines - UMAA, K.; RAMANATHAN, M.; KRISHNAKUMAR, K.; KANNAN, K. (Asian Journal of Chemistry, 2010)
The present work deals with the synthesis and characterization of seven substituted pyrimidines from chalcones. The chalcones that are prepared from substituted acetophenones and aromatic aldehydes with guanidine hydrochloride. The newly synthesized compounds were elucidated by using physical and spectral characteristics and the structures were established. The compounds were evaluated for antimicrobial and antimycobacterial potentials using Kirby bauer method and Alamar blue assay technique.